Characterisation of Static Liquefaction of Sand with Different Mixtures of Fines - Sabbar, Ayad Salih (Curtin University, 2018)
Liquefaction is a phenomenon of a sudden reduction in shear strength of saturated soils when subjected to undrained static or cyclic loading. Static liquefaction susceptibility of sand with various amounts of fines was investigated using experimental and artificial intelligence approaches. Liquefaction behaviour of sandy soils was considerably dependent on the fines content and fines types. The artificial intelligence results showed that both of ANN and GP could well predict the liquefaction susceptibility of mixtures.